Successful Treatment of Persistent Postcholecystectomy Bile Leak Using Percutaneous Cystic Duct Coiling - Rai, Vinay (Case Rep Surg, 2015)
Laparoscopic cholecystectomy is one of the most commonly performed operations worldwide. Cystic duct is the most common site of bile leak after cholecystectomy. The treatment of choice is usually conservative. Using sufficient percutaneous drainage of the biloma cavity and endoscopic retrograde cholangiography (ERCP) with sphincterotomy and/or stenting, the cure rate of bile leaks is greater than 90%. In very rare cases, all of these measures remain unsuccessful. We report a technique for the successful treatment of persistent cystic duct leak. After failed ERCP and stenting, bile leak was treated by coiling the cystic duct through a drain tract. This technique is safe and effective and helps avoid the morbidity of reoperation.